Semantic Comparison of Online Texts for Historical and Newly Constructed Replica Ancient Towns from a Tourist Perception Perspective: A Case Study of Tongguan Kiln Ancient Town and Jinggang Ancient Town - Ruimin Guo; Yiwen He; Xin Zhang; Lai He; Qixuan Zhou; Guojing He (Land)
This study explores the dimensions of visitor perception by conducting a semantic analysis, Grounded Theory coding classification, and sentiment analysis on online texts related to Jinggang Ancient Town and Tongguanyao Ancient Town. It reveals the differences between newly constructed and historical ancient towns in terms of tourism experience perception, landscape spatial design, and the activation of cultural heritage preservation. The results indicated the following: (1) The differences in tourists’ perceptions stem from the different needs for the characteristics of the ancient towns. Tourists focus on the design innovation and experiential interest of Tongguanyao Ancient Town, while preferring the cultural depth and authenticity of Jinggang Ancient Town. (2) Tourists are highly concerned about the characteristics of “tourism development”, highlighting the challenge of balancing tourism development with the protection of ancient town heritage resources. (3) The study further emphasizes innovative forms of the reproduction of cultural heritage through multi-sensory, modern, and diverse approaches. This study enhances landscape design in ancient towns by integrating perspectives from both tourists and designers, promoting the protection of cultural heritage and facilitating deeper cultural tourism integration.